A review of the mechanism and optimization of metal-assisted chemical etching and applications in semiconductors - Kibum Jung; Jungchul Lee (Micro and Nano Systems Letters, 2024)
Abstract Metal-Assisted Chemical Etching (MACE) is a technique for precisely forming nanostructures on semiconductor substrates, and it is actively researched in various fields such as electronic devices, optoelectronic devices, energy storage, and conversion systems. This process offers economic efficiency and effectiveness because it can be performed in a simple chemical laboratory environment without the need for expensive equipment. Particularly, MACE is recognized as an excellent technology for forming various nanostructures due to its advantage of precisely controlling the shape, size, and orientation of nanostructures compared to traditional etching techniques. MACE operates by inducing electrochemical reactions using a metal catalyst, selectively etching the semiconductor surface in a mixed solution of hydrofluoric acid (HF) and hydrogen peroxide ( $$\hbox {H}_2\hbox {O}_2$$ H 2 O 2 ). The metal catalyst reacts with the oxidant to generate holes, which are injected into the semiconductor substrate to promote oxidation reactions. The oxidized material is then dissolved by HF, progressing the etching process. Precise nanostructures are formed only in the areas with the metal catalyst, and the etching results vary depending on the type, thickness, and deposition method of the catalyst. In this study, we comprehensively review the mechanism of the MACE process, the patterns of nanostructure formation according to the characteristics of catalysts and substrates, and the influence of process variables. We also analyze application cases of MACE in various semiconductor substrates such as silicon (Si), germanium (Ge), indium phosphide (InP), and gallium arsenide (GaAs), and examine the latest research trends and applications utilizing MACE. Nanostructures formed through MACE have the potential to maximize the performance of next-generation semiconductor and optoelectronic devices, and research in this area is expected to greatly contribute to the future development of the semiconductor industry.